Productivity of Boran cattle maintained with chemoprophylaxis under high tsetse challenge at Mkwaja ranch in Tanzania. 2. Productivity - Trail, J.C.M.; Murray, M.; Sones, Keith R.; Jibbo, J.M.C.; Durkin, J.W.; Light, D.E. (1985)
ILRAD and ILCA, in collaboration with Amboni Limited (owners of Mkwaja Ranch) and May and Baker Limited, carried out an analysis of matching animal health, animal productivity and trypanocidal drug treatment data based on more than 20,000 calving records at Mkwaja Ranch over the 10 year period from 1973 to 1982. The performance traits analysed included cow reproduction, cow and calf viability, calf growth and cow weight. These characteristics were combined to build up an index including total weight of weaner calf produced per unit metabolic weight of cow per year calculated on a herd basis. On Mkwaja Ranch, the age of first calving was around 47 months and the calving percentage was 75%. The average weaning weight at 8 months was 134 kg, while the mean weight of cows was 286 kg. The pre-weaning annual mortality was 8.9% and adult cow mortality was 5.8%. The herd productivity, as assessed by the weight of 8 month old weaner calf produced per 100 kg .73 (metabolic weight) of cow per year, was 137.8 kg. In order to achieve this the mean number of treatments of Samorin over a complete calving interval of 485 days was 5.8, i.e., animals were treated on average every 83 days. The mean number of Berenil treatments was 0.8, i.e., treatments every 580 days. Despite such extensive use of trypanocidal drugs, it was concluded on the basis of productivity indices that there was no indication of toxic side effects or of the development of drug resistance. In order to put the productivity achieved at Mkwaja Ranch into perspective, the productivity indices were compared with those achieved on 11 Boran Ranches in tsetse-free areas of Kenya. It was found that grade Boran at Mkwaja were approximately 80% as productive as purebred Kenya Boran reared on ranches considered among the best in the world. In conclusion, cattle production under chemoprophylaxis is possible in areas heavily infested with tsetse. The fact that this result is based on one of the largest data sets ever analysed offers immediate hope for increased exploitation of tsetse-infested areas by encouragement of the rational use of trypanocidal drugs as an integral part of management. These findings should also stimulate pharmaceutical companies and international agencies to develop new and improved trypanocidal drugs.